Anal Eroticism with plastic bottle ways of management: A Case Report - Mathi M; Arun A; Nelson R; Andre Das; Umaparan G (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2017)
Foreign bodies in the rectum often pose a challenging diagnostic and management dilemma that begins with the initial evaluation in the emergency department and continues through the post extraction period. Because of the wide variety of objects and the variation in trauma caused to local tissues of the rectum and distal colon, a systematic approach to the diagnosis and management of rectal foreign bodies is essential. We present a case of 34 year old gentleman presented to emergency department with complaint of constipation for 2 days and claims he had inserted a plastic bottle in his anus 2days ago and unable to remove it. After failure of extraction of the bottle trans-anally and endoscopically, a mini laparotomy and incision on the sigmoid colon done to remove the foreign body. Patient was referred to the psychiatrist for his perversion disorder, which was also mandatory for preventing recurrences.